2022
DOI: 10.3389/fped.2021.728382
|View full text |Cite
|
Sign up to set email alerts
|

Changing Epidemiology of Acute Respiratory Infections in Under-Two Children in Dhaka, Bangladesh

Abstract: Objectives: Risk factors for acute respiratory infections (ARIs) in community settings are not fully understood, especially in low-income countries. We examined the incidence and risk factors associated with ARIs in under-two children from the Microbiota and Health study.Methods: Children from a peri-urban area of Dhaka (Bangladesh) were followed from birth to 2 years of age by both active surveillance of ARIs and regular scheduled visits. Nasopharyngeal samples were collected during scheduled visits for detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have investigated the associations between SDoH and health outcomes (i.e. diarrhoea, fever, cough and ARI) among U5y in Bangladesh [7,8,14,15,[24][25][26][27][28][29]. They have found that child's age [7,8,14,28,29], child's gender [7,14,15], mother's employment [28], father's occupation [24], housing conditions [28], and low birth weight [29] are associated with ARI among U5y in the country.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have investigated the associations between SDoH and health outcomes (i.e. diarrhoea, fever, cough and ARI) among U5y in Bangladesh [7,8,14,15,[24][25][26][27][28][29]. They have found that child's age [7,8,14,28,29], child's gender [7,14,15], mother's employment [28], father's occupation [24], housing conditions [28], and low birth weight [29] are associated with ARI among U5y in the country.…”
Section: Introductionmentioning
confidence: 99%
“…diarrhoea, fever, cough and ARI) among U5y in Bangladesh [7,8,14,15,[24][25][26][27][28][29]. They have found that child's age [7,8,14,28,29], child's gender [7,14,15], mother's employment [28], father's occupation [24], housing conditions [28], and low birth weight [29] are associated with ARI among U5y in the country. Similarly, low socio-economic status measured by the household wealth index [8,14,15,24,25,27,28], parental education [8,14,24,27], rural residency and regional differences [8] are associated with fever, ARI, diarrhoea, and cough in U5y.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal food and nutritional health play a significant outcome in early infancy (0-6 months) by influencing breast milk quality and output and restricting milk antibody transmission. Thereafter, the kid gets more exposed to the external world, and it is believed that water, sanitation and hygiene (WASH) and other environmental elements exert a greater influence 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on Riskesda 2013, the prevalence of ARI in children aged 1-4 years reached 25.8%. Environmental factors have a very large influence on the incidence of ARI, excessive dust content [6], [7], [8], [9], [10], air ventilation [11], [12], [13], [14], [15], lighting [16], and humidity [17], [18], [19], [20], [21] believed to be the cause of ARI, including ventilation which functions as an inlet and outlet of the air in the room. Natural or artificial lighting can directly or indirectly illuminate the entire room with an intensity of at least 60 Lux provided it creates glare.…”
Section: Introductionmentioning
confidence: 99%